Parenting Styles, Career Decision Self-Efficacy, and Career Exploration Behavior in Vocational High-School Students [Pola Asuh Orangtua, Efikasi-Diri Keputusan Karier, dan Perilaku Eksplorasi Karier pada Siswa Sekolah Menengah Kejuruan] - Melly Preston; Rose Mini Agoes Salim (ANIMA Indonesian Psychological Journal, 2019)
As an adaptive behavior, career exploration needs to be developed in vocational students who have difficulty in getting a job. The more career-related information obtained, the more likely it is for them to find the right job or the one that has the desired impact. To develop career exploration behavior in vocational students, it is necessary to know the factors that play a role in improving career exploration behavior. This study examined the mediating role of career decision self-efficacy in the relationship between parenting styles and career exploration behavior. Participants in this study were 824 senior vocational high school students from nine schools in Jakarta and Depok. The Parental Authority Questionnaire, Career Decision Self-Efficacy Scale-Short Form, and Career Exploration Survey were used to measure parenting styles, career decision self-efficacy and career exploration behavior. The results showed that career decision self-efficacy fully mediated the influenced of authoritative parenting styles in mothers and fathers on career exploration behavior in vocational students. Interestingly, the authoritarian parenting style was also found to have a positive and significant influence on career exploration behavior in vocational students. The implication and limitation are discussed. Sebagai perilaku adaptif, eksplorasi karier perlu dikembangkan pada siswa kejuruan yang mengalami kesulitan dalam mendapatkan pekerjaan. Semakin banyak informasi tentang karier yang diperoleh, semakin mungkin bagi mereka untuk menemukan pekerjaan yang tepat atau pekerjaan yang membawa dampak yang diinginkan. Untuk mengembangkan perilaku eksplorasi karier pada siswa kejuruan, maka perlu diketahui faktor-faktor yang berperan dalam mengembangkan perilaku eksplorasi karier. Studi ini menguji peran efikasi-diri keputusan karier dalam memediasi hubungan antara pola asuh orangtua dan eksplorasi karier. Partisipan dalam studi ini merupakan 824 siswa Sekolah Menengah Kejuruan dari sembilan sekolah di Jakarta dan Depok. Untuk mengukur pola asuh orangtua, efikasi-diri keputusan karier, dan eksplorasi karier, penelitian ini menggunakan Parental Authority Questionnaire, Career Decision Self-Efficacy Scale Short-Form, dan Career Exploration Survey. Hasil uji menunjukkan bahwa efikasi-diri keputusan karier memediasi secara penuh pengaruh pola asuh otoritatif dari ayah dan ibu terhadap eksplorasi karier siswa kejuruan. Menariknya, penelitian ini juga menemukan bahwa pola asuh otoritarian berpengaruh positif terhadap eksplorasi karier siswa kejuruan. Implikasi dan limitasi penelitian didiskusikan. Received 4 March 2019; Accepted 21 July 2019; Published 25 October 2019.